A novel multi-drug metronomic chemotherapy significantly delays tumor growth in mice. Issue 1 (December 2016) - Tagliamonte, Maria; Petrizzo, Annacarmen; Napolitano, Maria; Luciano, Antonio; Rea, Domenica; Barbieri, Antonio; Arra, Claudio; Maiolino, Piera; Tornesello, Marialina; Ciliberto, Gennaro; Buonaguro, Franco; Buonaguro, Luigi
Abstract Background The tumor immunosuppressive microenvironment represents a major obstacle to an effective tumor-specific cellular immune response. Methods In the present study, the counterbalance effect of a novel metronomic chemotherapy protocol on such an immunosuppressive microenvironment was evaluated in a mouse model upon sub-cutaneous ectopic implantation of B16 melanoma cells. The chemotherapy consisted of a novel multi-drug cocktail including taxanes and alkylating agents, administered in a daily metronomic fashion. The newly designed strategy was shown to be safe, well tolerated and significantly efficacious. Results Treated animals showed a remarkable delay in tumor growth and prolonged survival as compared to control group. Such an effect was directly correlated with CD4+ T cell reduction and CD8+ T cell increase. Furthermore, a significant reduction in the percentage of both CD25+ FoxP3+ and CD25+ CD127low regulatory T cell population was found both in the spleens and in the tumor lesions. Finally, the metronomic chemotherapy induced an intrinsic CD8+ T cell response specific to B16 naturally expressed Trp2 TAA. Conclusion The novel multi-drug daily metronomic chemotherapy evaluated in the present study was very effective in counterbalancing the immunosuppressive tumor microenvironment. Consequently, the intrinsic anti-tumor T cell immunity could exert its function, targeting specific TAA and significantly containing tumor growth. Overall, the results show that this represents a promising adjuvant approach to significantly enhance efficacy of intrinsic or vaccine-elicited tumor-specific cellular immunity.